EMPOWERING ECONOMIC GROWTH: THE VITAL ROLE OF MICROFINANCE IN REDUCING UNEMPLOYMENT IN SOMALIA (American International Journal of Business and Management Studies, 2022)
This study investigates how microfinance might help Somalia's unemployment rate decline. In many developing nations, microfinance has been acknowledged as a powerful tool for reducing poverty and fostering economic growth. The impact of microfinance on Somalia's unemployment rate is examined in this essay. Widespread acceptance of microfinance as a technique for reducing poverty and promoting economic growth in developing nations. The high unemployment rate in Somalia has posed a significant obstacle to the nation's economic development and social stability. This study looks at how microfinance could encourage small business growth and entrepreneurship in Somalia while lowering unemployment rates. The study looks at the difficulties faced by Somalia's microfinance organizations and how they affect efforts to lower unemployment. Additionally, it explores the connection between microfinance and job creation as well as the ways in which it might encourage entrepreneurship and the growth of small businesses. According to the study's findings, microfinance has the potential to significantly contribute to lowering Somalia's unemployment rate by facilitating access to capital, encouraging entrepreneurship, and generating employment possibilities. Yet, overcoming the difficulties faced by microfinance institutions in Somalia, such as poor infrastructure, a lack of regulatory framework, and political instability, is essential to the success of microfinance in lowering unemployment.JEL Classification Codes: G32, F65, L66, L25, M41.